Success Rates of Conventional Versus Endoscope-Assisted Probing for Congenital Nasolacrimal Duct Obstruction in Children 12 Years and Younger - Galindo-Ferreiro, Alicia; Akaishi, Patricia; Cruz, Augusto; Khandekar, Rajiv; Dossari, Saif; Dufaileej, Mohammed; Galvez-Ruiz, Alberto; Schellini, Silvana [UNESP] (Slack Inc, 2016)
Purpose: To compare the success rates for congenital nasolacrimal duct obstruction (CNLDO) treated with conventional probing versus endoscope-assisted probing. Methods: A retrospective nonrandomized comparison of the success rates in children (0 to 12 years) with CNLDO who underwent conventional probing or endoscope-assisted probing. Success was defined as absence of tearing or negative fluorescein dye disappearance test. Stent was evaluated. Results: A total of 270 patients with CNLDO comprised the study population. The mean age was 37 months in the conventional probing group and 48.5 months in the endoscope-assisted probing group. The subjective and objective success rates were 76.1% and 75.9%, respec-tively, in the conventional probing group and 95.7% and 95.7%, respectively, in the endoscope-assisted probing group. The success rates were higher for both methods in the endoscope-assisted probing group (P <.005). The success rate decreased in older children in the conventional probing group (100% < 6 months; 62.5% > 48 months) and remained stable in the endoscope-assisted probing group (100% < 6 months; 97% > 48 months). Stent did not improve success. Conclusions: Endoscope-assisted probing increased success in older children and children with bilateral obstruction.